Sustainable development goals in teacher education: comparing syllabi in a Japanese and a Slovenian university - Fiel’ardh, Khalifatulloh; Torkar, Gregor; Rožman, Hana; Fujii, Hiroki (Frontiers in Education, 2023)
Introduction This research aims to explore the integration of Sustainable Development Goals (SDGs) within teacher education programs, focusing on the Faculty of Education at Okayama University, Japan and the University of Ljubljana, Slovenia. Methods We employed a qualitative content analysis of the syllabi (n = 2,079 from Okayama University; n = 504 from University of Ljubljana) and combined it with insights from semi-structured interviews. Results The analysis illuminated a strong emphasis on Quality Education (SDG 4) in both institutions. However, certain SDGs, like Climate Action (SDG 13), were less represented, marking potential areas for enhancement. Differences were also identified in the distribution of SDGs-related content between compulsory and elective courses, indicating institutional priorities. Interview reflections emphasized the pivotal role of educators in realizing SDGs and highlighted the necessity of collaboration to achieve these global objectives. Discussion The insights from interviews and syllabi content analysis underscore the urgency to bridge the identified gaps in SDG coverage. Disparities in emphasis between the two Education for Sustainable Development (ESD)-committed universities were noted, suggesting the importance of fostering strategy exchange and partnerships across institutions. Conclusion Enhancing the alignment of teacher education programs with SDGs requires collective efforts. By addressing the gaps and promoting effective collaboration, these programs can achieve greater relevance and efficacy in promoting the SDGs.